2006
DOI: 10.1016/j.brainres.2006.03.108
|View full text |Cite
|
Sign up to set email alerts
|

Rapid discrimination of visual scene content in the human brain

Abstract: The rapid evaluation of complex visual environments is critical for an organism's adaptation and survival. Previous studies have shown that emotionally significant visual scenes, both pleasant and unpleasant, elicit a larger late positive wave in the event-related brain potential (ERP) than emotionally neutral pictures. The purpose of the present study was to examine whether neuroelectric responses elicited by complex pictures discriminate between specific, biologically relevant contents of the visual scene an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 33 publications
8
38
0
Order By: Relevance
“…This discrimination was present in the early time window of the P1 component of the ERP -a proximal index of attention allocation -and even more pronounced in the later endogenous component of the P3 -functionally considered response-related (decision-making). The findings are in line with previous research (Radilovà, Figar, & Radil, 1984;Anokhin et al, 2006), suggesting that the human brain is able to discriminate rapidly between specific contents of visual settings. Also in line with previous research (Bernat et al, 2001;Ito, Cacioppo, & Lang, 1998;Smith, Cacioppo, Larsen & Chatrand, 2003) is the finding that negative pictures elicited a more positive amplitude than positive and neutral ones.…”
Section: Studysupporting
confidence: 82%
“…This discrimination was present in the early time window of the P1 component of the ERP -a proximal index of attention allocation -and even more pronounced in the later endogenous component of the P3 -functionally considered response-related (decision-making). The findings are in line with previous research (Radilovà, Figar, & Radil, 1984;Anokhin et al, 2006), suggesting that the human brain is able to discriminate rapidly between specific contents of visual settings. Also in line with previous research (Bernat et al, 2001;Ito, Cacioppo, & Lang, 1998;Smith, Cacioppo, Larsen & Chatrand, 2003) is the finding that negative pictures elicited a more positive amplitude than positive and neutral ones.…”
Section: Studysupporting
confidence: 82%
“…In this regard the LPP has been mainly related to emotional processing (Cuthbert et al, 2000;Ferrari et al, 2011;Righi et al, 2012) reflecting the level of arousal triggered by the stimulus (Anokhin et al, 2006;Schupp et al, 2004;Hajcak et al, 2006). Overall, our results indicated that between 300 and 750 ms the processing of both affordance and attractiveness exerted an additive reinforcement in the processing of tools simultaneously evaluated as high attractive and high affording.…”
Section: Discussionmentioning
confidence: 59%
“…First of all, the communicative condition may differ from the private condition in terms of its emotional content, or simply the arousal that it elicits (Krämer et al 2010;Anokhin et al 2006). For example, the stimuli in the communicative condition appear more humorously than those of the private condition.…”
Section: Discussionmentioning
confidence: 99%